Interventions into students’ academic performance at HOTS levels in redox reactions using problem-based learning and peer-tutoring strategies - Kwasi, Benjamin N.; Achor, Emmanuel E. (Univeritas Papua, 2025)
The impact of problem-based learning and peer-tutoring strategies on the higher-order thinking performance of grade ten students in redox reactions in Kogi State, Nigeria, was explored using a quasi-experimental design of pretest-posttest unequal group setting. The population comprised 795 grade 10 students from 33 co-educational schools, out of which 146 students (males = 69, females = 77) emerged as the sample. Data were collected using the Higher Order chemistry Performance Test (HOCPT) with a reliability coefficient of 0.83. Mean, SD, bar charts, and ANCOVA were deployed for analysis. Both problem-based learning and peer-tutoring strategies considerably enhanced students' academic performance at higher-order thinking levels in redox reactions. Gender was not a determining factor in the effectiveness of these strategies, and a considerable interaction effect was not observed between strategies and gender. These findings suggest that problem-based learning and peer tutoring are effective in improving students' HOTS performance in chemistry, regardless of gender. Organization of training workshops to help chemistry teachers with the skills needed to implement activity-based instructional strategies effectively was recommended.